2017
DOI: 10.1080/02770903.2016.1266496
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding associated with higher lung function in African American youths with asthma

Abstract: Objective In the United States, Puerto Ricans and African Americans have lower prevalence of breastfeeding and worse clinical outcomes for asthma compared with other racial/ethnic groups. We hypothesize that history of breastfeeding is associated with increased forced expiratory volume in 1 second (FEV1) % predicted and reduced asthma exacerbations in Latino and African American youths with asthma. Methods As part of Study A and Study B, we conducted case-only analyses in children and adolescents aged 8–21 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…Results of studies showed a correlation between high sugar-sweetened beverages consumption and later asthma diagnosis. 32 One such study found that children from ages 2 to 9 years (a similar age group to our cohort) who consumed sugar sweetened beverages more than five times a week led to an adjusted odds of asthma that was five times greater than their counterparts who only consumed a maximum of one sugarsweetened beverage per month (OR 5.29; p ϭ 0.012). 33 However, our study was the first, to our knowledge, to indicate that sugar-sweetened beverages consumption may be related to a later asthma diagnosis, possibly through altering the risk for obesity.…”
Section: Sugar-sweetened Beverages Consumptionsupporting
confidence: 54%
See 1 more Smart Citation
“…Results of studies showed a correlation between high sugar-sweetened beverages consumption and later asthma diagnosis. 32 One such study found that children from ages 2 to 9 years (a similar age group to our cohort) who consumed sugar sweetened beverages more than five times a week led to an adjusted odds of asthma that was five times greater than their counterparts who only consumed a maximum of one sugarsweetened beverage per month (OR 5.29; p ϭ 0.012). 33 However, our study was the first, to our knowledge, to indicate that sugar-sweetened beverages consumption may be related to a later asthma diagnosis, possibly through altering the risk for obesity.…”
Section: Sugar-sweetened Beverages Consumptionsupporting
confidence: 54%
“…14,20 The role of breast-feeding as a protective factor against asthma development in girls indicates the need to support breast-feeding in high-risk minority communities and in those with low breast-feeding rates. 32 Our study indicated that breast-feeding rates were lower among children who had any reported asthma. Further, analysis of our results indicated that extending the time of breast-feeding by even 6 months had significant mitigating effects of the risk of asthma development in girls.…”
Section: Breast-feedingmentioning
confidence: 55%
“…At the beginning of the last century, Grulee and Sanford suspected a link between HM substitute feeding and a higher incidence of eczema [ 35 ]. Since then many prospective and retrospective observational studies have tested breastfeeding associations with the onset of allergic disease, providing mixed results for eczema [ 19 , 20 , 21 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] sensitisation [ 21 , 37 , 42 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and asthma [ 19 , 20 , 21 , 36 , 42 , 47 , 48 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Messages culminating from these studies range from a protective...…”
Section: Breastfeeding and Immunological Outcomesmentioning
confidence: 99%
“…A systematic review concluded that prolonged and exclusive breastfeeding is beneficial for the lung function up to 18 years of age, showing an improved lung function, with the most consistent finding related to increased FVC [ 13 ], while studies in adults appeared conflicting towards supporting this long-lasting relationship [ 32 , 33 ]. In addition, large cross-sectional trials in children and adolescents with asthma have shown that breastfeeding is associated with a higher FEV1 and reduced number of exacerbations [ 34 ], and that the FEV1 and FVC values in later life are correlated significantly with the duration of breastfeeding [ 35 ]. A good knowledge of the beneficial effects of PEB may lead to the adaptation of efficacious promoting strategies.…”
Section: Discussionmentioning
confidence: 99%